BEBERAPA SEGI KEMUKJIZATAN ALQURAN - Moh. Arsyad Ba'asyien (State Institute of Islamic Studies (IAIN) Palu, 2008)
The i’jâz of the Qur’an, which scholars define as the idea that the Qur’an constitutes something exceeding the customary, associated with challenge (tahaddî) and yet free from opposition, has received much attention from classical times to the modern era. Scholars have tried to determine what aspects of the Qur’an constitute i’jâz. Some of them have argued that language structure is an aspect of its i’jâz; some have pointed out that another aspect of i’jâz is the information provided about concealed events, including the stories about previous prophets and information about future events. Nevertheless, for the purpose of this article, the writer will discuss three aspects of i’jâz of the Qur’an only.Kata Kunci: i’jâz, kemukjizatan Alquran, mukjizat kebahasaan, mukjizat peristiwa masa lampau